2019
DOI: 10.1111/exd.13911
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the immune landscape in atopic dermatitis: The era of biologics and emerging therapeutic approaches

Abstract: Atopic dermatitis (AD) is a chronic, systemic, inflammatory disease that affects the skin and is characterized by persistent itch and marked redness. AD is associated with an increased risk of skin infections and a reduced quality of life. Most AD treatment options to date were not designed to selectively target disease‐causing pathways that have been established for this indication. Topical therapies have limited efficacy in moderate‐to‐severe disease, and systemic agents such as corticosteroids and immunosup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
157
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(163 citation statements)
references
References 155 publications
0
157
0
6
Order By: Relevance
“…68 A similar retrospective study reported that after 8-12 weeks of treatment, 36.8% of patients treated with methotrexate for hand eczema showed a good effect of treatment. 71 The general safety precautions with methotrexate therapy should be observed, such as monitoring the serum liver enzymes and complete blood count, as well as the cumulative dosage; a weekly dose of 30 mg should not be exceeded.…”
Section: Methotrexatementioning
confidence: 99%
“…68 A similar retrospective study reported that after 8-12 weeks of treatment, 36.8% of patients treated with methotrexate for hand eczema showed a good effect of treatment. 71 The general safety precautions with methotrexate therapy should be observed, such as monitoring the serum liver enzymes and complete blood count, as well as the cumulative dosage; a weekly dose of 30 mg should not be exceeded.…”
Section: Methotrexatementioning
confidence: 99%
“…They probably have a pathogenic role, triggering eosinophil and mast cells degranulation, and their titre seems to correlate with disease activity (Cozzani, Gasparini, Di Zenzo, & Parodi, 2018;Maglie & Hertl, 2019). IgE subtype antibodies are known to be associated with Th2 cells regulation, via IL-4 and IL-13 stimulation (Moyle et al, 2019). In fact, BP patients show a predominant type-2 response, suggesting that Th2 cells are primary involved in the loss of tolerance against BP180 (Cozzani et al, 2018;Maglie & Hertl, 2019).…”
Section: Bullous Pemphigoidmentioning
confidence: 99%
“…Circulating IgE anti-BMZ were also detected (Corti et al, 2018). The production of IgE class antibodies is well known to be amplified by both IL-4 and IL-13 stimulation (Moyle et al, 2019). At least for ocular MMP, three distinct pathogenic phases are described: the injury phase, with autoantibodies binding to autoantigens, activating an immunological cascade; then the acute inflammation phase, with neutrophils and proinflammatory cytokines (IL-1, TNFa, and IL-17) playing a crucial role, while Th1 cells produce IL-2 and interferon gamma, and Th2 cells release IL-4, IL-5, and IL-13; the production of these Th2-related cytokines leads to the fibrosis phase, with fibroblasts proliferating and producing extracellular matrix, connective tissue growth factor and TGFβ, causing fibrosis and mucosal scarring (Georgoudis et al, 2019).…”
Section: Mucous Membrane Pemphigoidmentioning
confidence: 99%
See 2 more Smart Citations